(untitled) (REMUNOM, 2023)
Morus nigra L., popularly known as black mulberry, has aroused interest due to its potential therapeutic benefits, especially in the context of insulin resistance. Several compounds present in this plant have been studied, revealing properties that may contribute to the improvement of insulin sensitivity. Among these compounds, flavonoids, anthocyanins, and polyphenols stand out, which have antioxidant and anti-inflammatory properties. The therapeutic action of these components seems to modulate metabolic pathways related to glucose control and lipid metabolism, promoting a more favorable environment for insulin sensitivity. The general objective of the present study was to discuss the therapeutic action of compounds present in Morus Nigra L. in insulin resistance. The present study is an integrative review and is considered an important tool in the health area, as it synthesizes the available research on a given topic and directs the practice based on scientific knowledge. It is a method that, through the synthesis of knowledge and incorporation of results, results in the reduction of biases and errors. Based on the guidelines and standards of the Brazilian Association of Standards and Techniques. The insertion of the descriptors in the databases resulted in the location of 102 productions, 53 in the VHL and 49 in the PUBMED. Therefore, Morus nigra L. stands out as a potential source of compounds with therapeutic action on insulin resistance, offering a promising approach in the prevention and treatment of type 2 diabetes and its complications. With their effects on glycemic regulation, lipid metabolism, gut microbiota, and gut barrier integrity, the compounds present in black mulberry represent a valuable prospect for improving the health and quality of life of individuals affected by this metabolic condition.